2019
DOI: 10.1002/biof.1505
|View full text |Cite
|
Sign up to set email alerts
|

Nodal increases the malignancy of childhood neuroblastoma cells via regulation of Zeb1

Abstract: Neuroblastoma (NB) is one of the most common malignant tumors derived from pluripotent cells of the neural crest. Nodal is an important embryonic morphogen which can re-express in cancer cells. The roles of Nodal in the progression of NB are not illustrated. Our present study reveals that Nodal is upregulated in NB cells and tissues. Targeted inhibition of Nodal can suppress the in vitro migration and invasion of NB cells while increase its chemo-sensitivity to doxorubicin (Dox) treatment. Nodal positively reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…These data are consistent with our previous observation that reduction in invasion, upon pharmacological and genetic inhibition of the ACVR1C receptor, correlated with decrease in ZEB1 and Snail protein levels, in multiple retinoblastoma lines [3]. Other studies have shown that Nodal controls migration and invasion in several tumor types by modulating the expression of Snail, Slug and ZEB1 [8, 10, 12, 36]. We therefore postulate that ZEB1 and Snail might mediate, at least in part, the effects of Nodal signaling on invasion, as we observed that knock down of Nodal, besides reducing ZEB1 and Snail, significantly inhibited metastatic potential both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with our previous observation that reduction in invasion, upon pharmacological and genetic inhibition of the ACVR1C receptor, correlated with decrease in ZEB1 and Snail protein levels, in multiple retinoblastoma lines [3]. Other studies have shown that Nodal controls migration and invasion in several tumor types by modulating the expression of Snail, Slug and ZEB1 [8, 10, 12, 36]. We therefore postulate that ZEB1 and Snail might mediate, at least in part, the effects of Nodal signaling on invasion, as we observed that knock down of Nodal, besides reducing ZEB1 and Snail, significantly inhibited metastatic potential both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…TGF-β1 can trigger EMT in neuroblastoma. In fact, E-cadherin significantly decreases, whereas α-SMA significantly increases after neuroblastoma cells are treated with different concentrations of TGF-β1 [78] and increase Slug and Zeb-1 expression [79]. Both N-Myc and c-Myc proteins in NB can bind and activate the TWIST1 promoter.…”
Section: Neuroblastomamentioning
confidence: 95%
“…Nodal can increase the malignancy of neuroblastoma cells by enhancing ZEB1 activity. Knockdown of ZEB1 attenuates Nodal-induced malignancy, and Nodal increases the protein stability of ZEB1 via phosphorylation mediated by Ataxia telangiectasia mutated kinase (ATM), rather than affecting its mRNA expression [107]. In human SH-SY5Y cells, miR-205 is positively regulated by Angelica polysaccharide and targets ZEB1 [108].…”
Section: Neuroblastomamentioning
confidence: 99%